Mallorca acne (actinic folliculitis). - Garofalo, L. (European Journal of Pediatric Dermatology, 2015)
Mallorca acne takes its name from the observation of Hjorth et Al. (1) who noticed its manifestations in Scandinavian subjects who had worked in Mallorca. The skin disorder begins in late spring, reaches the peak in the summer and then regresses spontaneously; the low-necked and deltoid region are mainly affected. The characteristic lesions are 2-3 mm diameter monomorphic erythematous follicular papules that rarely have a central pustule and are not associated with blackheads. There was much discussion on its pathogenesis: the hot and humid climate, the application of sunscreen and actinic radiation, also artificial (2) were assumed to play a role. In our two cases, the sharp saving of the areas covered by bra straps or by a jewel argue for the pathogenetic importance of actinic radiation.